GYNECOLOGY AND REPRODUCTOLOGY: : DIAGNOSIS, TREATMENT AND INNOVATIVE APPROACHES - Olimjonova, M.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This scientific work highlights modern diagnostic, treatment methods, and approaches in gynecology and reproductive medicine. It analyzes the most effective methods for maintaining women's health and restoring fertility. Additionally, factors affecting reproductive health and ways to eliminate them are discussed.